Controlling na potrzeby działalności marketingowej przedsiębiorstwa - Jaworska, Elżbieta (Controllership for the marketing activity in a corporate, 2006)
The article presents the issues of a firm’s goals and the role of these goals in a company. Achievement of company goals requires customer-oriented thinking. In this context, the paper also demonstrates the essence of the marketing controllership and the information system which is used for marketing management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 143-150